LESSONS LEARNED FROM COVID-19 PANDEMICS IN MALAYSIA’S FACILITIES MANAGEMENT ORGANISATION - Ahmad Sekak, Siti Nor Azniza; Mohamad Sha’aizam, Nurul Syahirah Qasrina; C. Alih, Suzana (PLANNING MALAYSIA, 2024)
The COVID-19 pandemic necessitates a significant response from the construction industry. The increasing recognition of the virus's transmission has demanded the enhancement of quality in multiple domains. The primary responsibility of Facilities Management (FM) is to guarantee the operational effectiveness, comfort, security, environmental friendliness, and productivity of the constructed surroundings. This paper seeks to examine the lessons learned from measures implemented by FM organisations during the COVID-19 pandemic. This research employs a quantitative methodology approach. The questionnaires were disseminated to 317 FM firms in Selangor with a response rate of 36%. The results found that most facilities managers had an ample understanding of FM organisation management throughout the pandemic. It is of utmost importance to comprehensively ascertain the lessons learned in FM during the COVID-19 pandemic and proactively equip and strategize themselves to handle future pandemics and disruptions by cultivating the capacity and resilience to respond to environmental shocks. The implementation of the plan is of utmost importance as it serves as a guiding principle for future actions. The endeavour and the knowledge gained from past pandemics have shaped an industry proposition for a fair and impartial approach to addressing future pandemics in Malaysia.